2
$\begingroup$

Find an explicit formula for a function that is exactly equivalent to the power series $$\sum_{n=1}^\infty\frac{(-1)^n}{2n+1}x^{2n}$$

Can somebody give me an idea on where to start with this?

Edit: Thanks to everybody's comments, I recognize that this power series is similar to the one for arctan:

$$\tan^{-1}x=\sum_{n=0}^\infty\frac{(-1)^n}{2n+1}x^{2n+1}$$

Please let me know if what I did was correct:

I decided to try and get the $x^{2n}$ in the first power series to $x^{2n+1}$ by multiplying the power series by $\frac{x}{x}$ to get:

$$\sum_{n=1}^\infty\frac{(-1)^n}{2n+1}\frac{x^{2n+1}}{x}$$

I then factored out $\frac{1}{x}$ to get:

$$\frac{1}{x}\sum_{n=1}^\infty\frac{(-1)^n}{2n+1}{x^{2n+1}}$$

Considering that $\sum_{n=1}^\infty a_n=\bigg(\sum_{n=0}^\infty a_n\bigg)-a_0$ this would mean that:

$$\frac{1}{x}\sum_{n=1}^\infty\frac{(-1)^n}{2n+1}{x^{2n+1}}=\frac{1}{x}\bigg(\sum_{n=0}^\infty\frac{(-1)^n}{2n+1}x^{2n+1}-x\bigg)$$

Which makes the power series equivalent to:

$$\frac{1}{x}(\tan^{-1}x-x)$$

$\endgroup$
2
$\begingroup$

Your work is correct. As an alternative approach that avoids recognizing the Maclaurin series for $\arctan$, it is easy to note that $\frac1{2n+1}=\int_0^1t^{2n}~\mathrm dt$, hence with geometric series and the derivative of $\arctan$,

\begin{align}\sum_{n=1}^\infty\frac{(-1)^n}{2n+1}x^{2n}&=\int_0^1\sum_{n=1}^\infty(-1)^nx^{2n}t^{2n}~\mathrm dt\\&=\int_0^1\sum_{n=1}^\infty(-x^2t^2)^n~\mathrm dt\\&=\int_0^1\frac{-x^2t^2}{1+x^2t^2}~\mathrm dt\\&=\int_0^1\frac1{1+x^2t^2}-1~\mathrm dt\\&=\frac1x\arctan(x)-1\end{align}

$\endgroup$
1
$\begingroup$

To find a closed form for a power series it is often interesting to find a differential equation verified by the function. Not also that it works both ways, since given an ODE we can try to find a power series verifying it and that gives relations between coefficients.

Anyway, here the first thing to notice is that the $2n+1$ denominator can be cancelled by derivation of $x^{2n+1}$.

And since we only get $x^{2n}$ on numerator we ought to multiply the whole thing by $x$.

Thus $\quad xf(x)=x\sum\limits_{n=1}^{\infty} \dfrac{(-1)^n x^{2n}}{2n+1}=\sum\limits_{n=1}^{\infty} \dfrac{(-1)^n x^{2n+1}}{2n+1}$

Now by derivating $\quad (xf(x))'=\sum\limits_{n=1}^{\infty} (-1)^n x^{2n}=\sum\limits_{n=1}^{\infty} (-x^2)^n\quad$ and we recognize a geometric sum.

Till now, we haven't paid much attention to convergence, but obviously the radius of convergence is $1$ so we will assume $|x|<1$ from now on.

The summation gives $(xf(x))'=\underbrace{(-x^2)}_{\text{sum starts at n=1}}\dfrac {1-0}{1-(-x^2)}=\dfrac {-x^2}{1+x^2}=\dfrac{1}{1+x^2}-1\quad$

[since $(-x^2)^N\to 0$]

Integrating this ODE leads finally to $xf(x)=\arctan(x)-x+C$

The power series gives initial condition $f(0)=0\implies C=0$ and we have found the closed form:

$$f(x)=\dfrac{\arctan(x)}x-1$$

$\endgroup$
  • $\begingroup$ No need to involve imagine numbers when you can write the geometric series as $\sum_{n=1}^\infty(-x^2)^n$ no? $\endgroup$ – Simply Beautiful Art May 9 at 12:59
  • $\begingroup$ Yep, it was late when I wrote it. Edited. $\endgroup$ – zwim May 9 at 19:00

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.